Proceedings of the 4th Padang International Conference on Education, Economics, Business and Accounting (PICEEBA-2 2019) 2020
DOI: 10.2991/aebmr.k.200305.169
|View full text |Cite
|
Sign up to set email alerts
|

The Development Strategy of Tourism Sector in Ponorogo, Indonesia

Abstract: This study aims to identify the priority strategies for developing the Ngebel Lake tourism object in Ponorogo Regency. This paper applied AHP method in determining the priority of appropriate policy strategies in developing the Ngebel Lake tourism object. This study took a sample of 30 respondents using purposive and incidental sampling techniques. The results showed that the infrastructure aspect is the priority policy criterion in developing tourism objects with the value of 0.424 while the lowest priority i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The factor which supports the potential of the KHDTK Oelsonbai area to be scientific tourism is its natural tourism potential. Sumarsono et al (2020) stated that in the context of developing tourism, it must be directed at the utilization of natural resources. Therefore, the object of tourism attraction in this study used the object of natural tourism attraction.…”
Section: Tourism Attraction Of Khdtk Oelsonbaimentioning
confidence: 99%
See 1 more Smart Citation
“…The factor which supports the potential of the KHDTK Oelsonbai area to be scientific tourism is its natural tourism potential. Sumarsono et al (2020) stated that in the context of developing tourism, it must be directed at the utilization of natural resources. Therefore, the object of tourism attraction in this study used the object of natural tourism attraction.…”
Section: Tourism Attraction Of Khdtk Oelsonbaimentioning
confidence: 99%
“…Good accessibility will help visitors reach the tourism location using various transportation methods. The development of tourism objects can be conducted by increasing facilities and infrastructures, such as repairing or widening road access to the location of tourism objects (Sumarsono et al 2020). Furthermore, improving the accessibility and infrastructure of the area around tourist attractions that is adapted to the local wisdom of the community, for example, the axis road to the location of the tourist attraction is more appropriate to make road rebates rather than paving the road (Nugroho et al 2015).…”
Section: Number Of Respondentmentioning
confidence: 99%
“…Lubis & Siregar (2021) in their study about Aspects of Civil Law in the Development of Culture-Based Tourism revealed that it needs to give legal protection in terms of safety and security for or visitors, both domestic tourists and foreign tourists. In addition, a study conducted by Sumarsono, Arti, & Soesilo (2020) 'The Development Strategy of Tourism Sector in Ponorogo, Indonesia mentioned that the effort to develop tourism objects is directed according to the criteria that are the priority of the strategy, namely the infrastructure aspect with the support of optimal promotion. Therefore, based on the background of this study above, the purpose of this study is to examine the legal basis for the development of a site into a tourist attraction.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the potential of natural resources and cultural diversity in eastern Indonesia is very potential to support this target. The diversity of natural resources in the eastern part of Indonesia has always been an attraction for tourists, both local and foreign tourists (Atmoko 2021;Kusniasanti, 2019;Sumarsono et al, 2020). However, not all tourism is managed and developed properly.…”
Section: Introductionmentioning
confidence: 99%
“…One of the obstacles is the low awareness of the community to participate (Asiabar, et al, 2021;Zhou et al, 2021). Human awareness and consolidation to promote the economy collectively, especially in human relations with nature is the basis for the realization of sustainable tourism (Sumarsono, et al, 2020;Indiarti & Munir, 2016).…”
Section: Introductionmentioning
confidence: 99%